A STUDY ON CUSTOMER SATISFACTION WITH REFERENCE TO VINAYAK BAKERY AND ITS COMPETITORS AT HALIYAL - S, Nitinchandra; Hunswadkar, Namita (International Journal of Engineering Technologies and Management Research, 2018)
This comparative study on Vinayak bakery is for understanding the position of Vinayak Bakery in the market relative to its competitors. It is the oldest Bakery in Haliyal and well known for its brand reputation. On the contrary we were able to understand the strategies rolled out by the competitors in the market. Consequently to determine the customer satisfaction at Haliyal a survey was conducted with sample size of 50 with the comparison of other bakeries’ products and other facilities as well.